Peningkatan Ekonomi Masyarkat Melalui Home Industry Pengrajin Boneka “Devista Toys” Di Cikampek Utara - Aulia Rahmawati, Indry; Yasmita, Dwi; Pertiwi Hari Sandi, Santi; Epty Hidayaty, Dwi (Rifa'Institute, 2023)
This home industry visit aims to find out how the process of improvement is obtained by the surrounding community who join the Devista Toys Home Industry. Unemployment is a social problem that greatly affects the economy in a region. Handling economic problems and unemployment needs to be done, for example by providing jobs. So one of the efforts to overcome unemployment, poverty and improve the community's economy is as carried out by Mr. Hj. Devis, who founded the Devista Toys Home Industry, became more productive and independent. Providing knowledge by holding training on sewing, decorating dolls, and packing dolls. This industrial visit used qualitative methods, namely observation and interviews to see how far the process was carried out by Devista Toys' Home Industry and see the results obtained by its employees. The results of this Home Industry visit show that the improvement process carried out by Home Industry has significant potential to improve the community's economy. Through skills training, improving product quality, access to a wider market, and forming networks,